An analysis of Undergraduates' Study Skills - Bulent, Alci; Hakan, Karatas; Aydin, Balyer (ELSEVIER SCIENCE BV, 2015)
There is a growing need for the integration of various theoretical perspectives on academic achievement such as study skills. Study skills are approaches applied to learning that assist students to be successful in schools in a way of passing an exam or even obtaining good grades. The purpose of this study was to determine the effect of undergraduates' study skills on academic achievement and significances in their study skills in terms of gender and department. The sample group of the study consists of 210 undergraduates studying in three different departments at School of Education. To determine their study skills, the data were collected using Study Skills Scale developed by Bay, Tugluk, and Gencdogan (2005). To determine the correlation between undergraduates' study skills and academic achievement, the analysis of Pearson correlation was used. Also, to determine significant differences in undergraduates' study skills regarding gender and departments, the analysis of independent samples of t-test and ANOVA were conducted. The results reveal that there is a positive correlation between study skills and academic achievement and also significant differences were found in undergraduates' study skills in terms of gender and departments. (C) 2015 Published by Elsevier Ltd.
Keywords: Study skills; undergraduates; gender; department; ACADEMIC-PERFORMANCE; TIME-MANAGEMENT; TEST ANXIETY; STUDENTS; MOTIVATION; METAANALYSIS; ACHIEVEMENT; STRATEGIES; ATTITUDES; STRESS; Education & Educational Research; Social Sciences - Other Topics